Transoral Robotic Surgery in the Nordic Countries: Current Status and Perspectives - Mäkitie, Antti A.; Keski-Säntti, Harri; Markkanen-Leppänen, Mari; Bäck, Leif; Koivunen, Petri; Ekberg, Tomas; Sandström, Karl; Laurell, Göran; von Beckerath, Mathias; Nilsson, Johan S.; Wahlberg, Peter; Greiff, Lennart; et al. (Frontiers in Oncology, 2018)
Background: The five Nordic countries with a population of 27M people form a rather homogenous region in terms of health care. The management of head and neck cancer is centralized to the 21 university hospitals in these countries. Our aim was to gain an overview of the volume and role of transoral robotic surgery (TORS) and to evaluate the need to centralize it in this area as the field is rapidly developing. Materials and Methods: A structured questionnaire was sent to all ten Departments of Otorhinolaryngology - Head and Neck Surgery in the Nordic countries having an active programme for TORS in December 2017. Results: The total cumulative number of performed robotic surgeries at these 10 Nordic centers was 528 and varied between 5-240 per center. The median annual number of robotic surgeries was 38 (range, 5-60). The observed number of annually operated cases remained fairly low (<25) at most of the centers. Conclusions: The present results showing a limited volume of performed operations call for considerations to further centralize TORS in the Nordic countries.